Differences in the function and secretion of congenital aberrant fibrinogenemia between heterozygous γD320G (Okayama II) and γΔN319-ΔD320 (Otsu I). Issue 6 (December 2015) - Mukai, Saki; Ikeda, Minami; Takezawa, Yuka; Sugano, Mitsutoshi; Honda, Takayuki; Okumura, Nobuo
Abstract: Background: We encountered two patients with hypodysfibrinogenemia and designated them as Okayama II and Otsu I. Although the affected residue(s) in Okayama II and Otsu I overlapped, functionally determined fibrinogen levels and the ratio of functionally to immunologically determined plasma fibrinogen levels were markedly different. Methods: DNA sequence and functional analyses were performed for purified plasma fibrinogen. A recombinant protein was synthesized in Chinese hamster ovary (CHO) cells to determine the secretion of variant fibrinogens. Results: A heterozygous A>G in FGG, resulting in γ320Asp>Gly for Okayama II, and a heterozygous deletion of AATGAT in FGG, resulting in the deletion of γAsn319 and γAsp320 (γΔN319-ΔD320) for Otsu I, were obtained. SDS-PAGE and Coomassie staining revealed that the variant γ-chain was not clear in Okayama II, but was clearly present in Otsu I. The lag period for the fibrin polymerization of Okayama II was slightly slower than that of the normal control, whereas Otsu I fibrinogen indicated no polymerization within 30 min. Both variant γ-chains were synthesized in CHO cells and assembled into fibrinogen; however, the fibrinogen concentration ratio of the medium/cell lysate of γ320Gly was six-fold lower than that of γΔN319-ΔD320. Conclusions: We concluded that the plasma fibrinogen of Okayama II, constituted by a lower ratio of the variant γ-chain, led to the almost normal functioning of fibrin polymerization. However, the plasma fibrinogen of Otsu I, with a higher ratio of the variant γ-chain, led to marked reductions in fibrin polymerization. Highlights: A heterozygous γ320Asp>Gly substitution was designated Okayama II. A heterozygous deletion of γAsn319 and γAsp320 was designated Otsu I. Okayama II (Ok) fibrin polymerization was almost normal. Otsu I (Ot) fibrin polymerization was markedly reduced. The proportion of the variant fibrinogen in plasma was higher in Ot than in Ok.